Seedling-stage salinity screening of Indonesian local rice varieties from Kalimantan and Lombok-Sumbawa - SITI ZAHARA; ETTY WAHYUNI; EKO HARY PUDJIWATI; NURHASANAH NURHASANAH; WIDI SUNARYO; RUSDIANSYAH RUSDIANSYAH; I GUSTI PUTU MULIARTA ARYANA; WAYAN WANGIYANA; SUKARTONO SUKARTONO (Asian Journal of Agriculture, 2026)
Abstract. Zahara S, Wahyuni E, Pudjiwati EH, Nurhasanah, Sunaryo W, Rusdiansyah, Aryana IGPM, Wangiana W, Sukartono. 2026. Seedling-stage salinity screening of Indonesian local rice varieties from Kalimantan and Lombok-Sumbawa. Asian J Agric 10 (2): g100202. https://doi.org/10.13057/asianjagric/g100202. Salinity stress constrains rice growth, and local germplasm may provide useful sources of tolerance. This study evaluated seedling-stage responses of 14 Indonesian local rice varieties from Kalimantan and Lombok-Sumbawa under hydroponic conditions and screened for the presence of two candidate salt-stress-related genes, OsAPX1 and DST. Pokkali (tolerant) and IR 29 (sensitive) were used as check varieties. Seedlings were exposed for seven days to Yoshida nutrient solution containing 0, 5000, or 10,000 ppm NaCl (0, 7.8, and 15.62 dS m-1). Shoot and root elongation, leaf chlorophyll content, shoot and root dry weight, and shoot and root tolerance indices were measured. Salinity significantly inhibited seedling growth and reduced chlorophyll content, with responses differing among varieties. Based mainly on root and shoot tolerance indices and comparison with check varieties, Adan Hitam (Nunukan), Padi Ikan (Bulungan), and Padi Alas Barat (Sumbawa) showed relatively higher tolerance under the screening conditions. The DST gene was detected in all local and check varieties, whereas OsAPX1 gene was detected in 13 local varieties and both checks but not in Mayas Pendek. These PCR results indicate only the presence or absence of expected amplicons and require expression or functional validation. The identified tolerant candidates may be useful preliminary materials for rice salinity-tolerance breeding.